2020
DOI: 10.1103/physrevb.101.014436
|View full text |Cite
|
Sign up to set email alerts
|

Zero-field propagation of spin waves in waveguides prepared by focused ion beam direct writing

Abstract: Metastable Fe78Ni22 thin films are excellent candidates for focused ion beam direct writing of magnonic structures due to their favorable magnetic properties. The focused ion beam transforms the originally nonmagnetic fcc phase into the ferromagnetic bcc phase with an additional control over the direction of uniaxial magnetic in-plane anisotropy and the saturation magnetization. The induced anisotropy allows to stabilize transverse direction of magnetization in narrow waveguides. Therefore, it is possible to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…[1][2][3] This expansion is triggered by the development of advanced synthesis methods 4,5 and the discovery of novel geometry-and topologyinduced effects. 6 Among the various nanofabrication techniques, focused electron beam-induced deposition (FEBID) has unique advantages for 3D nanomagnetism, 2,3,7 magnonics 8,9 and superconducting electronics of the fluxonic type 10,11 as the magnetic properties of direct-write structures can be varied by selecting a writing strategy and beam parameters, 5 as well as via post-growth irradiation of structures with ions [12][13][14] and electrons. 15 In the context of superconductivity, hybrid ferromagnet/superconductor structures are used for the manipulation of magnetic flux quanta 16,17 and provide access to investigations of odd-frequency spin-triplet superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This expansion is triggered by the development of advanced synthesis methods 4,5 and the discovery of novel geometry-and topologyinduced effects. 6 Among the various nanofabrication techniques, focused electron beam-induced deposition (FEBID) has unique advantages for 3D nanomagnetism, 2,3,7 magnonics 8,9 and superconducting electronics of the fluxonic type 10,11 as the magnetic properties of direct-write structures can be varied by selecting a writing strategy and beam parameters, 5 as well as via post-growth irradiation of structures with ions [12][13][14] and electrons. 15 In the context of superconductivity, hybrid ferromagnet/superconductor structures are used for the manipulation of magnetic flux quanta 16,17 and provide access to investigations of odd-frequency spin-triplet superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4]9,[28][29][30][31][32][33] For magnonics, the propagation of spin waves in direct-write Fe-and Co-based conduits has recently been demonstrated, with a spin-wave decay length in the range of 3-6 lm. 34,35 Given FEBID's lateral resolution down to 10 nm and its versatility regarding the substrate material, FEBID appears as a promising nanofabrication technology for 3D magnonics. 36 Here, we investigate the spin-wave eigenmodes in individual direct-write Co-Fe nanovolcanoes by spin-wave resonance (SWR) spectroscopy 37,38 and analyze the experimental data with the aid of micromagnetic simulations.…”
mentioning
confidence: 99%
“…This anisotropy is strong enough to stabilize the magnetization in the direction perpendicular to the long axis of narrow waveguides. It has been recently demonstrated that in this system, spin waves can propagate in favorable Damon-Eshbach mode with high group velocities reaching almost 6 km/s in orthogonally magnetised waveguides without the necessity of applying the external magnetic fields [199]. The magnetic anisotropy can also be used to stabilize various spin structures unachievable in common material systems, and these spin structures can be further used to control spin-wave propagation [200].…”
Section: F Spin-wave Propagation In Materials With Locally Controlled...mentioning
confidence: 97%